Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/egusphere-egu21-13101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid intensity variations during the second half of the first millennium BCE in Central Asia and global implications.

Abstract: <p>Recent archeomagnetic studies performed in different regions of the world have revealed unusual periods of sharp changes in intensity during the first millennium. Here we focus on the study of intensity variations between 600 BCE and 600 CE in central Asia, where an important intensity decrease seems to be present during the second half of the 1<sup>st</sup> millennium BCE. For this purpose, we present a new paleosecular variation (PSV) curve obtained from 51 new ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…In our previous study (Bonilla‐Alba et al., 2021), we already suggested that the V‐shaped intensity feature may have originated from a non‐dipole contribution of the geomagnetic field. The new intensity data acquired here further corroborate this V‐shaped pattern and contribute to a refined definition of the increasing branch by revealing high intensities at the end of the second century CE.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In our previous study (Bonilla‐Alba et al., 2021), we already suggested that the V‐shaped intensity feature may have originated from a non‐dipole contribution of the geomagnetic field. The new intensity data acquired here further corroborate this V‐shaped pattern and contribute to a refined definition of the increasing branch by revealing high intensities at the end of the second century CE.…”
Section: Discussionmentioning
confidence: 73%
“…Data are also compared with the paleosecular variation intensity curve proposed by Bonilla‐Alba et al. (2021) and the predictions of the most recent global geomagnetic field models: ArchKalMag14k.r (Schanner et al., 2022), SHAWQ‐Iron Age (Osete et al., 2020) and SHAWQ2k (Campuzano et al., 2019). All data and models are relocated to Termez (37.3°N, 67.2°E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations